Reinforcing Research in Higher Education for Quality Enhancement in Industry and Educational Institution - Devaraju, S.; Jawahar, S.; Harishchander, A. (Asian Review of Mechanical Engineering, 2021)
Higher Education is one way to acquire more knowledge and skills. This knowledge and skills are influenced by the students or employees learning to work with more ability in the industry for excellence rather than the survival. The Higher Education Institutions (HEIs) are working highly dynamic state all over the world. Most universities and autonomous institutions are reframing their curriculum and syllabus based on the industry requirements. The higher education institution should focus on quality of teaching through various teaching aids. This teaching aid helps the students to understand the concepts very clearly and it is possible to apply their knowledge at the industry environment. The industry also focuses on role ready engineers, though the institution and industry are working closely to produce the role read engineers. It is possible to improve the quality of the higher education teaching with research collaboration between the institution and industries. Industry always looks at the research areas based on the student or employee perception. The research is only the way to get more innovative ideas and new thoughts to produce the better quality education. Although it is necessary to retain an effective teaching through research at the institution and Industry environment.